Nanofibras de poliamida 6 produzidas por fiação por sopro em solução modificadas com materiais carbonáceos: caracterização e aplicação na remoção de poluentes orgânicos - Alvarenga, Augusto Duarte (Universidade Federal de São Carlos, 2021)
Emerging pollutants found in water resources have become a worldwide concern due to their potential toxicity and deleterious effects on both human health and the environment. This scenario has driven the search for alternatives aiming at the remediation of these compounds with high efficiency and low costs for applications in real situations. In this project we propose the development of polyamide 6 (PA6) nanofiber mats produced by the solution blow spinning method (solution blow spinning) modified with different carbonaceous materials, including: i) polystyrene soot, ii) graphene oxide, iii) reduced graphene oxide and iv) sugarcane bagasse fly ash and sugarcane bagasse fly ash thermally activated in CO2 atmosphere, and evaluation of their respective performance in the adsorption of organic pollutants. The materials produced were characterized by scanning electron microscopy (SEM), X-ray dispersive energy spectroscopy (EDS), mechanical dynamic analysis (DMA), thermogravimetric analysis (TGA), x-ray diffraction (XRD), infrared spectroscopy (FTIR), surface area analysis (BET), contact angle, zeta potential and particle size. The produced nanofiber mats were collected by a hollow rod collector, which provided a higher collection rate, ease recovery of the as-produced mats and contributed to the evaporation of the residual solvent. The average diameter of produced fibers varied from 139 to 456 nm. In relation to the adsorption capacity, the systems were evaluated in batch and in fixed bed adsorptions and indicated good correlation with the kinetic model of pseudo 2nd order kinetic model and Langmuir isothermal model for the platforms PA6 Soot, PA6GO and PA6rGO and good correlation with Freundlich model for the PA6 CVBCA platform. The PA6 CVBCA platform showed excellent performance in the adsorption of methylene blue reaching 186,46 mg g-1 relative efficiency in batches and 34,79 mg g-1 in fixed bed, indicating potential for application in real situations of contaminants removal from aquatic environments. It was also observed that the conditioning of sugarcane bagasse fly ash in ethanol could increase its relative efficiency by 30%. Finally, the PA6GO, PA6rGO, PA6 CVBC and PA6 CVBCA platforms maintained their efficiency up to the 15 th reuse cycle.
Polyamide 6 nanofibers produced by solution blow spinning modified with carbonaceous materials: characterization and application in the removal of organic pollutants
Poliamida 6 nanofibras producidas por blow spinning en soluciones modificadas con materiales carbonatos: caracterización y aplicación en la eliminación de contaminantes orgánicos
Keywords: Nanofibras; Fiação por sopro em solução; Adsorção; Grafeno; Carvão ativado; Fuligem; Nanofibers; Solution blow spinning; Adsorption; Graphene; Activated carbon; Soot; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::CINETICA QUIMICA E CATALISE; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::SEPARACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::NAO-METAIS E SEUS COMPOSTOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::CONTROLE DA POLUICAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::LIMPEZA PUBLICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::AGUA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::CARVAO; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::TEXTEIS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::TRATAMENTOS E APROVEITAMENTO DE REJEITOS; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS::TECNICAS AVANCADAS DE TRATAMENTO DE AGUAS